Influence of homogeneous–heterogeneous reactions on micropolar nanofluid flow over an exponentially stretching surface with the Cattaneo–Christov heat flux model - N. Ramya; M. Deivanayaki; P. Kavya; K. Loganathan; S. Eswaramoorthi (Discover Applied Sciences)
Abstract This study investigates the influence of homogeneous–heterogeneous reactions on micropolar nanofluid flow over an exponentially stretching surface, incorporating the Cattaneo–Christov heat flux model to capture non-Fourier heat conduction effects. The research systematically analyses key transport mechanisms, including thermophoresis, Brownian motion, and micropolar fluid parameters, to assess their impact on heat and mass transfer efficiency. The governing equations for momentum, microrotation, energy, and nanofluid concentration are reformulated into a dimensionless form using suitable transformations and numerically solved using MATLAB’s bvp4c solver, ensuring computational precision. Validation against existing literature confirms strong agreement with minimal discrepancies. The findings indicate that thermophoresis increases both temperature and nanofluid concentration distributions, while Brownian motion decreases the temperature and the nanoparticle concentration profiles. The effect of material parameter is also examined, revealing an increase in nanofluid concentration but a marginal suppression of temperature profiles. These insights are critical for engineering applications, such as nanofluid-based cooling systems, biomedical devices, and industrial thermal management, where precise control of thermal properties is essential.